Saryn in culture turkic peoplе (Journal of Oriental Studies, 2017)
Introducing advanced forms and varieties of oral folklore tradition preservedfor several centuries, the spiritual culture of Turks to the beginningof the third millennium presents a unique area human civilization. spiritualculture of the TurksIn this aspect, the article considers one of the earliest samples of folklore– saryn. The complex issues associated with the study of early music culture(in particular, saryn) can be developed based on the paradigms of prose,poetry, music examples (materials), as well as the archaeological data.